FlipGrid: Re-imagining online discussion forums for the public administration classroom. (2nd January 2023) - Rinfret, Sara R.; Forster, Elizabeth
ABSTRACT: Public administration faculty commonly use discussion forums in their asynchronous courses to engage students about course content. However, the typical pedagogical approach for online discussions forums is for the professor to post questions and students respond, in writing. In this paper, we suggest public administration classes should consider the use of FlipGrid for asynchronous course discussions because it engenders student participation through oral videos about course content. Our pilot study uses original data collected during a global pandemic (Spring 2021) to document the experiences of 39 students enrolled in two asynchronous public administration classes. The findings illustrate FlipGrid enhanced important skills for our public administration students – verbal communication skills (e.g. clarity and brevity) and ability to connect theory to practice.